GLOBALIZATION AND DEVELOPMENT OF INFRASTRUCTURE: THE CASE OF AGRICULTURAL MARKET - Denys Ilnytskyy; Dmytro Voichak (Izdevnieciba "Baltija Publishing", 2019)
The paper aims at investigation of factors that influence infrastructure development stakeholders in their search for reasoning the volumes of investments that globally lack 1 trln USD every year, which constitutes a problem for sustainable development of markets and regions. Development of infrastructure of agricultural sector of national and global economies has been taken as the object of the research. Market economy has never been able to develop infrastructure that could function on sustainable basis and the situation remain in times of globalization. Evolution of infrastructure has passed several stages since 1870 and led to increase in international trade, but it is still in need, when talking about global food security and global food problem. Research of infrastructure and its components is one of the objects that every year becomes the theme of increasing number of research papers. We propose four stages of development of global markets infrastructure - prerequisite, emergence, flourishment and dominance. Global agriculture markets infrastructure consists of several groups of structural components - trading, financial, social, institutional, information, scientific and educational, innovation and ecological. In our understanding the lack of complex development of all of these components lead to global food instability, market violations and sectoral crises. There is a matrix model of relationships of factors and infrastructure components of infrastructure market proposed. The specific purpose of the paper is to check the hypothesis which tells us that low or absent direct relationships between infrastructure development indicators and economy's ones lead to under-investments. The findings are that there are too low levels of correlation between a) infrastructure development indicators and GDP of countries; b) infrastructure development index in Ukrainian regions and their gross volume of agricultural production. We conclude that among factors of infrastructure development the major role play those that demonstrate indirect relationships.